Artificial Intelligence in Deepfake Technologies Based on Supply Chain Strategy - Alattas, Khalid; Bayoumi, Magdy (ExcelingTech, 2020)
It is highly impossible to differentiate between verified and fake media news and updates with modern emerging technology. The creation of deeper fake photos and videos which use artificial intelligence (AI), that shows someone saying and doing things that never did in reality, is one of the recent innovations that contribute to it. Concentrated depths will easily hit millions of citizens and affect adversely our culture, along with their accessibility and pace of social networking. This paper analyses a variety of widely accessible internet news stories, while literature on this subject is scarce, in order to explore the depths, and who creates them, how deep technological advantages and risks are, which example of deepfake occur and how the depths are to be gauged. We will use qualitative research methodology to gather the available information and based on the findings, in the end, we will conclude the discussions along with recommendations.